Analisis Perlindungan Konsumen Pada Penerapan Pembulatan Harga Barang Yang Dilakukan Oleh Pihak Penjual - Syamsiar Arief; Arry Wirrawan (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
This study provides a description of consumer protection for the right to change money in buying and selling transactions in several minimarkets in Makassar. This study aims to determine the form of payment transactions at minimarkets and the legal consequences of price fixing with unavailable nominal currency. This type of research is a qualitative research with a normative juridical approach through the methods of observation, interviews and documentation. The results obtained explain that several minimarkets as objects of research have implemented promotional methods to attract consumers' interest by applying nominal prices, which in fact some of them no longer exist in the use of currency in Indonesia such as Rp. 8.990,- (eight thousand nine hundred and ninety rupiah). In addition, sellers also often take advantage of rounding off prices, which basically can still be accommodated in currency denominations such as Rp. 9.900, - in which consumers often refuse a refund of Rp. 100,- or the seller replaces the change by using other products such as candy. This kind of trading practice According to Law Number 8 of 1999 there are 5 articles of violation, namely as follows: Violation of article 9 letter (a), article 10 letter (a), article 15, and related to sanctions for transferring change into candy based on the law Number 7 of 2011 then this has violated Article 8 of the UUPK, as a result of this violation can be punished with 5 years in prison or a maximum fine of Rp. 2,000,000,000 (two billion rupiah), as stated in Article 62 paragraph 1 of the UUPK. (3).